2011
DOI: 10.1007/s12663-011-0308-8
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglossal Schwannoma of Parapharyngeal Space: An Unusual Case Report

Abstract: Schwannomas are benign tumor of the schwann cells. These are common in eighth, tenth cranial nerves and parasympathetic chain. Hypoglossal schwannomas are rare. Among the hypoglossal schwannomas the intracranial and dumb-bell shaped schwannomas are frequent but extra cranial hypoglossal schwannomas are rare. We describe a parapharyngeal hypoglossal schwannoma in a 25 years female presenting as slow growing mass in right side of the neck.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
1
4
0
1
Order By: Relevance
“…Independently from the nerve that is affected, surgical treatment consists of systematic exeresis of the lesions. This has been furthermore confirmed by the experience of the present authors and by case reports (2,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)30,31). In fact, all except one of the cases were treated surgically.…”
Section: Imaging and Diagnosissupporting
confidence: 86%
See 1 more Smart Citation
“…Independently from the nerve that is affected, surgical treatment consists of systematic exeresis of the lesions. This has been furthermore confirmed by the experience of the present authors and by case reports (2,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)30,31). In fact, all except one of the cases were treated surgically.…”
Section: Imaging and Diagnosissupporting
confidence: 86%
“…In almost all cases, there are varying degrees of paresis of the HyN, which appear as ipsilateral deviation, hemiatrophy and fasciculations of the tongue. These symptoms may be accompanied by hoarseness, intermittent-to-persistent headaches, dysarthria, slurred speech, swallowing difficulties and throat cramps (2,4,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Whereas the effects on the specific functions of the nerve may be attributable to the local damage of the tumour on the nerve, these types of lesions, particularly when they increase in volume, may determine mass effects on surrounding or adjacent structures; for example, Mariniello et al (19) reported on the case of a patient who exhibited signs of cerebellar ataxia, right-sided hypotonia and increased intracranial pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Extracranial hypoglossal nerve schwannomas often present as a solitary, painless neck mass in the neck 11 . Most of the patients commonly have tongue deviation and speech disturbance, but small portion of the patients presented without any neurological symptoms 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Der N. facialis stellt ebenfalls einen häufig beschriebenen Ursprung für Schwannome des Kopf-Hals-Bereichs dar, deren Lokalisation häufig intraparotideal, im Bereich des Felsenbeins (Ganglion geniculi) oder am Kleinhirnbrückenwinkel liegt [7,8]. Deutlich seltener wurden Fälle von Schwannomen des N. hypoglossus publiziert [9].…”
Section: Introductionunclassified